AFROTROPICAL TYCHIUS: DESCRIPTION OF FIVE NEW SPECIES AND DESIGNATION OF A NEOTYPE (Coleoptera, Curculionidae) - Caldara, Roberto (Fragmenta entomologica, 2013)
Five new species belonging to the weevil genus Tychius are described: T. barclayi n. sp. (South Africa), T. gambiensis n. sp. (Gambia), T. muellerarum n. sp. (South Africa), T. rufotheivorus n. sp. (South Africa), T. stalsi n. sp. (South Africa). Moreover the neotype of T. suturellus Gyllenhal, 1836 is designated. Descriptions, photographs of their habitus and figures of rostra and genitalia are given.